2018
DOI: 10.1093/infdis/jiy563
|View full text |Cite
|
Sign up to set email alerts
|

Reviving Phage Therapy for the Treatment of Cholera

Abstract: Cholera remains a major risk in developing countries, particularly after natural or manmade disasters. Vibrio cholerae El Tor is the most important cause of these outbreaks, and is becoming increasingly resistant to antibiotics, so alternative therapies are urgently needed. In this study, a single bacteriophage, Phi_1, was used prophylactically and therapeutically to control cholera in an infant rabbit model. In both cases, phage-treated animals showed no clinical signs of disease, compared with 69% of untreat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 25 publications
0
28
0
2
Order By: Relevance
“…Due to rapid symptom development and the role of cholera toxin in the clinical syndrome, phage therapy might not be useful as a treatment for patients with symptomatic infections, although it may be used to control the spread of the disease such as prophylaxis for high‐risk individuals during an outbreak . Nevertheless, pre‐clinical data suggest that phage therapy may be used with therapeutic or prophylactic intent …”
Section: The Future Of Phage Therapy In Gastrointestinal Diseasesmentioning
confidence: 99%
“…Due to rapid symptom development and the role of cholera toxin in the clinical syndrome, phage therapy might not be useful as a treatment for patients with symptomatic infections, although it may be used to control the spread of the disease such as prophylaxis for high‐risk individuals during an outbreak . Nevertheless, pre‐clinical data suggest that phage therapy may be used with therapeutic or prophylactic intent …”
Section: The Future Of Phage Therapy In Gastrointestinal Diseasesmentioning
confidence: 99%
“…In the case of human cholera, there is the opportunity for breaking this cycle through treatment in hospitals or clinics where the faeces of the infected and treated individuals can be collected and composted. We and others have shown that lytic phage can be highly effective and reducing V. cholerae numbers in the gut and associated clinical signs using experimental animal infections (Bhandare et al 2018).…”
Section: Competitive Exclusion By Live Vaccinessomething New!?mentioning
confidence: 96%
“…As such, the replication of both B. bacteriovorus and phage may be subject to a minimum host/prey threshold, below which they cannot sustain their populations indefinitely. However, this may be therapeutically beneficial as elimination of a pathogen is often not necessary to achieve significant reductions or complete resolution of disease symptoms [63,94]. The host range of an individual phage is usually restricted to a number of strains within a species or one or two closely related species of bacteria, which makes the maintenance of their populations more challenging than B. bacteriovorus.…”
Section: Comparison To Other Microbiological Antibacterial Approachesmentioning
confidence: 99%